Lacticaseibacillus rhamnosus C1 effectively inhibits Penicillium roqueforti: Effects of antimycotic culture supernatant on toxin synthesis and corresponding gene expression - An, Peipei; Li, Li; Huang, Pei; Zheng, Yin; Jin, Zekun; Korma, Sameh A.; Ren, Namei; Zhang, Nan (Frontiers in Microbiology, 2023)
Recently, consumers are increasingly concerned about the contamination of food by molds and the addition of chemical preservatives. As natural and beneficial bacteria, probiotics are a prospective alternative in food conservation because of their antimycotic activities, although the mechanism has not been explained fully at the level of metabolites. This study aimed at investigating the antifungal activities and their mechanisms of five potential probiotic strains (Lacticaseibacillus rhamnosus C1, Lacticaseibacillus casei M8, Lactobacillus amylolyticus L6, Schleiferilactobacillus harbinensis M1 and Limosilactobacillus fermentum M4) against Penicillium roqueforti, the common type of mold growth on the bread. Results showed that C1 emerged the strongest effectiveness at blocking mycelium growth, damaging the morphology of hyphae and microconidia, decreasing DNA content and interfering in the synthesis of the fungal toxins patulin, roquefortine C and PR-toxin, as well as downregulating the expression of key genes associated with the toxin biosynthesis pathways. Further metabonomic investigation revealed that protocatechuic acid with the minimum inhibitory concentration of 0.40 mg/mL, may be most likely responsible for positively correlated with the antimycotic effects of C1. Thus, C1 is expected to be both a potentially greatly efficient and environmental antimycotic for controlling P. roqueforti contamination in foods.